Fuzzy-based decision analysis on Arctic transportation: A guidance for freight shipping companies - Lukas Benz; Christopher Münch; Evi Hartmann (Adapting to the Future: Maritime and City Logistics in the Context of Digitalization and Sustainability. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 32, 2021)
Purpose: Due to climate change the Arctic ice is melting, opening new possibilities for the economical use of the Arctic Ocean. However, the decision for shipping companies to transport freight through Arctic waters is based on many factors. The aim of the research is to develop a decision-supporting guidance for shipping companies. Methodology: Based on a literature review and subsequent validation through expert interviews, influencing factors are identified and classified using a framework covering Benefits, Opportunities, Costs, and Risks. A fuzzy set theory to structure multi-criteria decision problems is applied afterward. Findings: The results show that equipment, insurance, and inadequate port infrastructure are the factors with the highest influence in the Costs category and are the most influential factors overall. Security and market potential, the factors with the greatest impact on the Opportunities category, also rank highly as influential overall factors. The strongest Risk factors are weather conditions, delay, and collisions / accidents. The highest influence in the Benefits category are reduced costs. Originality: The influencing factors for Arctic freight shipping have so far only been considered in part with risks focus or other specific aspects, but not in the overall context. To consider multiple perspectives, 24 experts from different domains were involved.
urn:nbn:de:gbv:830-882.0162272; hdl:10419/249609; https://econpapers.repec.org/RePEc:zbw:hiclpr:32
Keywords: 650